Buckling-induced F-actin fragmentation modulates the contraction of active cytoskeletal networks. Issue 17 (11th April 2017) - Li, Jing; Biel, Thomas; Lomada, Pranith; Yu, Qilin; Kim, Taeyoon
Abstract : Actomyosin contractility originating from interactions between F-actin and myosin facilitates various structural reorganizations of the actin cytoskeleton. Abstract : Actomyosin contractility originating from interactions between F-actin and myosin facilitates various structural reorganizations of the actin cytoskeleton. Cross-linked actomyosin networks show a tendency to contract to single or multiple foci, which has been investigated extensively in numerous studies. Recently, it was suggested that suppression of F-actin buckling via an increase in bending rigidity significantly reduces network contraction. In this study, we demonstrate that networks may show the largest contraction at intermediate bending rigidity, not at the lowest rigidity, if filaments are severed by buckling arising from myosin activity as demonstrated in recent experiments; if filaments are very flexible, frequent severing events can severely deteriorate network connectivity, leading to the formation of multiple small foci and low network contraction. By contrast, if filaments are too stiff, the networks exhibit minimal contraction due to the inhibition of filament buckling. This study reveals that buckling-induced filament severing can modulate the contraction of active cytoskeletal networks, which has been neglected to date.